Parahydrogen based NMR hyperpolarisation goes micro: an alveolus for small molecule chemosensing. Issue 3 (10th January 2019) - Bordonali, Lorenzo; Nordin, Nurdiana; Fuhrer, Erwin; MacKinnon, Neil; Korvink, Jan G.
Abstract : We implemented continuous-flow SABRE NMR spectroscopy on a chip, unlocking low-volume chemosensing of strongly diluted analytes. Abstract : Complex mixtures, commonly encountered in metabolomics and food analytics, are now routinely measured by nuclear magnetic resonance (NMR) spectroscopy. Since many samples must be measured, one-dimensional proton (1D 1 H) spectroscopy is the experiment of choice. A common challenge in complex mixture 1 H NMR spectroscopy is spectral crowding, which limits the assignment of molecular components to those molecules in relatively high abundance. This limitation is exacerbated when the sample quantity itself is limited and concentrations are reduced even further during sample preparation for routine measurement. To address these challenges, we report a novel microfluidic NMR platform integrating signal enhancement via parahydrogen induced hyperpolarisation. The platform simultaneously addresses the challenges of handling small sample quantities through microfluidics, the associated decrease in signal given the reduced sample quantity by Signal Amplification by Reversible Exchange (SABRE), and overcoming spectral crowding by taking advantage of the chemosensing aspect of the SABRE effect. SABRE at the microscale is enabled by an integrated PDMS membrane alveolus, which provides bubble-free hydrogen gas contact with the sample solution. With this platform, we demonstrate high field NMR chemosensing of microliter sample volumes, nanoliter detection volumes, and micromolar concentrations corresponding to picomole molecular sensitivity.